2022
DOI: 10.3390/nu14235016
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maternal B Vitamins in Early Pregnancy and Gestational Diabetes Mellitus: A Prospective Cohort Study

Abstract: Background: This study evaluated the association between maternal B vitamins in early pregnancy and gestational diabetes mellitus (GDM) risk. Methods: A cohort of 1265 pregnant women was recruited at 8–15 weeks of gestation in 2021–2022 (Shanghai, China). Pregnancies with both serum B vitamin measurements at recruitment and glucose measurements at 24–28 weeks of gestation were included in the final analysis. Results: Of the 1065 pregnancies, in the final analysis, GDM occurred in 121 women (11.36%). In multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Besides, the establishment of the association of the metabolic status of nutritional indicators with the impact on disease risk may provide valuable insights into the physiopathologic interpretation of the illness as well as the optimal nutritional management [18 -20]. Nevertheless, the reports on the correlation between the status of multiple nutritional metabolites during the early stage of pregnancy with the adverse outcomes were still limited [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the establishment of the association of the metabolic status of nutritional indicators with the impact on disease risk may provide valuable insights into the physiopathologic interpretation of the illness as well as the optimal nutritional management [18 -20]. Nevertheless, the reports on the correlation between the status of multiple nutritional metabolites during the early stage of pregnancy with the adverse outcomes were still limited [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…A group of the important bacteriome‐derived metabolites is the B vitamins including pyridoxine (vitaminB6), folic acid (vitaminB9) and cobalamin (vitaminB12) which are de-novo synthesized by the gut microbiota [ 134 , 135 ]. Previous studies in women with GDM indicated a higher level of folate during second or third trimester in which the higher maternal folate status combined with the B12 insufficiency can predict a higher risk of GDM [ 136 139 ]. In contrast, some studies revealed that Folic acid supplementation can protect early pregnant women from the risk of GDM, however, the exact dose or duration is yet to be identified [ 140 ].…”
Section: Introductionmentioning
confidence: 99%